Going Full Circle: Demand-Side Constraints to the Green Paradox - Corrado Di Maria; Ian A. Lange; Edwin van der Werf (Center for Economic Studies and ifo Institute (CESifo), 2013)
We argue that the literature on the green paradox has largely ignored the demand side of the resource market, and that this side of the market may mitigate the size of an emissions increase in response to imperfect climate policies. These claims are informed by recent empirical findings. Our arguments lead to clear policy recommendations.
Keywords: Q31; Q38; Q58; 330; green paradox; climate policy; demand side response